Global Change and Mountain Regions An Overview of Current Knowledge - Huber, Uli M.; Bugmann, Harald K. M.; Reasoner, Mel A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Mountain regions occupy about a quarter of the global terrestrial land surface and provide goods and services to more than half the humanity. Global environmental change threatens the integrity of these systems and their ability to provide the goods and services upon which humanity has come to depend. This book gives an overview of the state of research in fields pertaining to the detection, understanding and prediction of global change impacts in mountain regions. More than 60 contributions from paleoclimatology, cryospheric research, hydrology, ecology, and development studies are compiled in this volume, each with an outlook on future research directions.
From the contents: Introduction. T. Hofer; The International Year of Mountains, Challenge and opportunity for mountain research -- Part I: Paleoenvironmental Changes -- Part II: Cryospheric Changes -- Part III: Hydrological Changes -- Part IV: Ecological Changes -- Part V: Human Dimensions -- Synthesis -- A. Björnsen, U. M. Huber, M. Reasoner, B. Messerli, H. Bugmann; Future research direction.
Keywords: ENVIRONMENTAL SCIENCES; CLIMATIC CHANGES; ENVIRONMENT; ENVIRONMENT, GENERAL; CLIMATE CHANGE